MEMODELKAN PROFITABILITAS BANK BPD DI INDONESIA - PRATAMA, I WAYAN RIAN; SUCIPTAWATI, NI LUH PUTU; SUSILAWATI, MADE (E-Jurnal Matematika, 2022)
Bank in general have a function to move economy of a country, so they required to be in good physical condition in order to execute their purposes directly. The value of bank performance and soundness level can be measured using several ratios, one of which is net interest margin (NIM). NIM in Indonesia’s Bank until 2019 is the highest among ASEAN countries. The purpose of the research is modeling also determining the significant factors that affect the profitability of Bank for Regional Development (BPD) in Indonesia. The results show that the chosen model to model the open unemployment rate in Indonesia is a panel data model with the effect of time with  of 32.47% and significant affect by BOPO.